2017
DOI: 10.1182/blood-2017-02-765891
|View full text |Cite
|
Sign up to set email alerts
|

Treating sickle cell disease by targeting HbS polymerization

Abstract: Although the root cause of sickle cell disease is the polymerization of hemoglobin S (HbS) to form fibers that make red cells less flexible, most drugs currently being assessed in clinical trials are targeting the downstream sequelae of this primary event. Less attention has been devoted to investigation of the multiple ways in which fiber formation can be inhibited. In this article, we describe the molecular rationale for 5 distinct approaches to inhibiting polymerization and also discuss progress with the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
234
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(240 citation statements)
references
References 110 publications
5
234
0
1
Order By: Relevance
“…This study provides only in vitro evidence and is limited to the investigation of blood samples from six individuals with SCT. The effect of 5HMF even at or near 0% measured oxygen tension is surprising but consistent with a reported direct oxygen-independent influence of allosteric effectors of haemoglobin on polymer stability (Eaton & Bunn, 2017) and also consistent with prior reports that GBT440, a compound with a similar mechanism of action, reduces the sickled cell fraction at 0% measured oxygen . Because oxygen tension in vivo rarely drops below even 1% oxygen (Spencer et al, 2014), the precise nature of 5HMF's effects under absolute anoxic conditions may not be physiologically relevant.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study provides only in vitro evidence and is limited to the investigation of blood samples from six individuals with SCT. The effect of 5HMF even at or near 0% measured oxygen tension is surprising but consistent with a reported direct oxygen-independent influence of allosteric effectors of haemoglobin on polymer stability (Eaton & Bunn, 2017) and also consistent with prior reports that GBT440, a compound with a similar mechanism of action, reduces the sickled cell fraction at 0% measured oxygen . Because oxygen tension in vivo rarely drops below even 1% oxygen (Spencer et al, 2014), the precise nature of 5HMF's effects under absolute anoxic conditions may not be physiologically relevant.…”
Section: Discussionsupporting
confidence: 90%
“…The effect of 5HMF, even when oxygen is undetectable, is surprising. This finding may partly reflect a direct effect on polymer stability previously described for allosteric effectors like 5HMF (Eaton & Bunn, 2017). It is also possible that, despite an absence of oxygen in the source gas, a small amount of oxygen below the limit of detection of the oxygen sensor is diffusing into the system from the environment.…”
Section: Hmf Significantly Reduces the Maximal Rheological Response mentioning
confidence: 78%
“…There is thus cause for optimism, as there are several mechanisms for increasing delay times other then by increasing fetal hemoglobin synthesis. [67][68][69] These are described in detail in a recent Blood perspective, 70 so they will only be mentioned here. They include increasing cell volume to decrease HbS concentration, binding a drug to the R conformation, thereby shifting the T-R equilibrium toward the non-polymerizing R conformation, decreasing intracellular 2,3-diphosphoglycerate (2,3-DPG) to destabilize the fiber and shifting the quaternary equilibrium toward R, increasing intracellular pH (2,3-DPG also increases intracellular pH), and destabilizing the fiber by binding a drug to block intermolecular contacts.…”
Section: Targeting Polymerization For Drug Therapymentioning
confidence: 99%
“…In conclusion, wide variations in practice utilizing IVFs are common. [18][19][20] We recently showed that increased extracellular fluid tonicity and sodium levels can negatively impact sRBC deformability and adhesion in in vitro models. seek emergency department (ED) care.…”
Section: Funding Informationmentioning
confidence: 99%
“…Ultimately this could improve deformability and allow sRBCs to escape the capillary bed, before deoxygenation can cause Hb-S polymerization and vaso-occlusion. [18][19][20] We recently showed that increased extracellular fluid tonicity and sodium levels can negatively impact sRBC deformability and adhesion in in vitro models. 21 Given the growing controversy surrounding ED use of IVF boluses, we recently investigated the use of IVF to treat VOE in pediatric patients with sickle cell anemia (SCA) presenting to the three EDs at Children's Healthcare of Atlanta, where guidelines discourage the use of NSB in euvolemic patients with uncomplicated, moderate-severe VOE.…”
Section: Funding Informationmentioning
confidence: 99%